Determination of Generator Losses and Efficiency - Klasnić, Ilija G; Ćirić, Zoran; Bogdanović, Slobodan; Džepčeski, Dane; Joksimović, Dušan; Arnautović, Dušan (Proceedings, Electrical engineering institute "Nikola Tesla", 2015)
The paper presents the results of deriving by calculation the local and total losses of the generator as well as efficiency determination of the revitalised hydro-generator unit A4 in HPP "Djerdap 1". In order to determine the generator losses and generator efficiency, measurements are performed during the acceptance tests of revitalised aggregate A4 in HPP "Djerdap 1"